Stratifin Promotes Hepatocellular Carcinoma Progression by Modulating the Wnt/β-Catenin Pathway - Shan-Ping Ye; Hong-Xin Yu; Wei-Jie Lu; Jun-Fu Wang; Tai-Yuan Li; Jun Shi; Xiao-Ye Cheng (International Journal of Genomics)
Abnormal stratifin (SFN) expression is closely related to the progression of several human cancers, but the potential roles of SFN in hepatocellular carcinoma (HCC) remain largely unknown. In this study, we found that SFN was upregulated in HCC cell lines and tissues and was positively associated with tumor size, poor differentiation, Tumor Node Metastasis (TNM) stage, and vascular invasion. In addition, high expression levels of SFN were associated with poor overall survival and disease-free survival. Biologically, downregulation of SFN suppressed tumor cell proliferation, epithelial–mesenchymal transition (EMT), invasion, and migration in vitro and tumor growth in vivo. However, overexpression of SFN promoted cell proliferation, EMT, invasion, and migration in vitro and tumor growth in vivo. Mechanistically, overexpression of SFN activated the Wnt/β-catenin pathway by promoting Glycogen synthase kinase-3 beta (GSK-3β) phosphorylation, decreasing β-catenin phosphorylation, promoting β-catenin transport into the nucleus, and enhancing the expression of c-Myc, whereas depletion of SFN inhibited the Wnt/β-catenin pathway. In addition, TOPFlash/FOPFlash reporter assays showed that overexpression or downregulation of SFN obviously increased or decreased, respectively, the activity of the Wnt/β-catenin pathway. Our results indicated that SFN plays an important role in HCC, possibly providing a prognostic factor and therapeutic target for HCC.